ECLS in Pediatric Cardiac Patients - Di Nardo, Matteo; MacLaren, Graeme; Marano, Marco; Cecchetti, Corrado; Bernaschi, Paola; Amodeo, Antonio (Frontiers in Pediatrics, 2016)
Extracorporeal Life Support (ECLS) is a valuable tool in the management of neonates and older children with severe cardiac or respiratory failure. In this review, we focus on ECLS when used for neonatal and pediatric cardiac disease. Strict selection of patients and timely deployment are necessary to optimize outcomes. Although every attempt should be made to deploy ECLS urgently rather than emergently, extracorporeal cardiopulmonary resuscitation (ECPR) is being increasingly used and reasonable survival rates have been achieved after initiation of ECLS during active compressions of the chest following in-hospital cardiac arrest. Contraindications to ECLS are falling over time, although lethal chromosomal abnormalities, severe irreversible brain injury, and extremely low gestational age and weight (<32 weeks gestation or <1.5 kg) remain firm contraindications.